Upaya Meningkatkan Hasil Belajar Kelas XI MIPA-3 melalui Aplikasi Google Classroom di SMA Negeri 1 Purwoasri - Siti Nur Afifah; Ayusantia Ayusantia (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to improve the learning outcomes of grade XI MIPA-3 students at SMA Negeri 1 Purwoasri in Islamic Education and Ethics through the use of the Google Classroom application. The method used was Classroom Action Research (CAR) conducted in two cycles. Data collection techniques included observation, interviews, documentation, and tests. The results of the study showed a significant increase in student learning outcomes in each cycle, marked by increased student activity, participation in discussions, and test scores that exceeded the Minimum Completion Criteria (KKM). The conclusion of this study confirms that the application of Google Classroom as an online learning medium is effective in improving the quality of learning and student learning outcomes.